Sealing device with high surface roughness

By using the functional layer and barrier layer of the highly filled thermoplastic polymer composition in the sealing device, the surface roughness is improved in combination with the foam extrusion process, the problem of insufficient adhesion strength between the waterproof film and concrete is solved, and efficient concrete combination is achieved and waterproof effect.

CN114728494BActive Publication Date: 2024-12-31SIKA TECH AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080078144.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-18
Filing Date
2020-12-09
Publication Date
2024-12-31
Estimated Expiration
2040-12-09

AI Technical Summary

Technical Problem

The early adhesion strength of the existing waterproof membrane to concrete in pre-applied applications is insufficient, resulting in detachment after the concrete is hardened, affecting the waterproof performance of the building structure.

Method used

Using a sealing device containing a functional layer and a barrier layer of a highly filled thermoplastic polymer composition, the surface roughness of the functional layer is improved through the foam extrusion process and the adhesion strength to the concrete is enhanced.

Benefits of technology

It achieves high early adhesion strength after concrete hardening within 24 hours, avoids the risk of formwork detachment, reduces production costs, and improves waterproofing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114728494B_ABST
    Figure CN114728494B_ABST
Patent Text Reader

Abstract

The present invention relates to a sealing device comprising a functional layer (2) having a first main surface and a second main surface and a barrier layer (3) directly or indirectly connected to the second main surface of the functional layer (2), wherein the functional layer (2) has a surface roughness characterized by a waviness factor Wf. The present invention also relates to a method for producing the sealing device and the use of the sealing device for waterproofing a substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to sealing devices for use in the construction industry for waterproofing underground or above-ground building structures. In particular, the present invention relates to sealing devices that can be used to protect basements, roofs and tunnel structures from water penetration. Background Art

[0002] In the field of construction, polymer sheets, often referred to as membranes or panels, are used to protect underground and above-ground structures, such as basements, tunnels and roofs from water penetration. Waterproofing membranes are applied, for example, to prevent water intrusion through cracks that develop in concrete structures due to building settlement, load deflection or concrete shrinkage. Roofing membranes are used for waterproofing flat and low-slope roof structures. Prior art waterproofing and roofing membranes are single-layer or multi-layer systems comprising at least one polymer-based barrier layer to provide watertightness.

[0003] The commonly used material of barrier layer comprises plastic, particularly thermoplastic such as plasticized polyvinyl chloride (p-PVC), thermoplastic polyolefin (TPO) and elastomer such as ethylene-propylene diene monomer (EPDM).Thermoplastic polyolefin is a heterogeneous polyolefin composition containing a high crystallinity base polyolefin and a low crystallinity or amorphous polyolefin modifier.The film based on crosslinked EPDM is very flexible and weather-resistant, but they are not heat-weldable due to the chemically crosslinked structure.The film consisting of TPO can be heat-welded and more expensive than EPDM-film, but they are also slightly more rigid, which can be a disadvantage in some applications.The film based on plasticized PVC is more flexible than TPO film, but they contain environmentally harmful plasticizers and heavy metal additives such as flame retardants, which can limit their use in some applications.

[0004] In waterproofing applications, the membrane can be post-applied to an existing concrete structure or pre-applied prior to building the concrete structure to be waterproofed. In the first case, the membrane is adhered to the surface of the concrete structure to be waterproofed by means of an adhesive layer or by using a sealing tape. In pre-applied waterproofing applications, the membrane is placed with its barrier layer facing the surface of the underlying structure or formwork, and fresh concrete is then poured on the surface of the opposite surface of the membrane, thereby completely and permanently bonding the membrane to the surface of the hardened concrete.

[0005] One of the well-known disadvantages of polymer-based barriers is their poor bonding properties; they typically show low bonding strength with adhesives commonly used in the construction industry, such as epoxy adhesives, polyurethane adhesives and cementitious compositions. Therefore, a contact layer such as wool felt is typically used to improve the bonding of the polymer-based barrier to the structure to be waterproofed. Some commercially available membranes for pre-applied waterproofing applications comprise a barrier layer and a nonwoven fabric layer as a contact layer, which is adhered to the barrier layer by an adhesive layer. The adhesive layer is used to fix the contact layer to the barrier layer, but it is also possible to improve the bonding between the barrier layer and the fresh concrete cast on the contact layer. However, the presence of the adhesive layer increases the production cost of these types of waterproof membranes and the nonwoven fabric layer, which is typically wool, actually prevents the sealing of the seam formed by heat welding between the overlapping edges of the membrane.

[0006] Patent application WO2017 / 108843A1 discloses a waterproof membrane comprising a polymer-based barrier layer and a contact layer composed of a thermoplastic polymer composition, the thermoplastic polymer composition comprising a large amount of inorganic fillers such as inorganic binders. The waterproof membrane can be produced by coextruding a melt-processed composition of a barrier layer and a functional layer and bonding the layers thus obtained to each other, for example, using a calendering cooling roll. The waterproof membrane disclosed in WO2017 / 108843A1 provides high adhesion strength to concrete in a pre-applied waterproof application when concrete is poured on the surface of the contact layer and allowed to harden for 28 days under normal atmospheric conditions. Despite the high bonding strength established with fresh concrete after hardening, it was also found that the waterproof membrane of WO2017 / 108843A1 provides a non-optimal early adhesion strength to the poured concrete, i.e., the obtained adhesion strength, allowing the poured concrete to harden for one day under normal atmospheric conditions. The low early adhesion strength to the poured concrete can cause the pre-applied waterproof membrane to detach, because the formwork used in the casting of the concrete structure, such as the base plate, is usually removed after 24 hours of hardening of the poured concrete.

[0007] There is therefore a need for new waterproofing membranes that develop high early adhesion strength with fresh concrete poured on the membrane surface in pre-applied waterproofing applications. SUMMARY OF THE INVENTION

[0009] The object of the present invention is to provide a sealing device which can be used, for example, in basement waterproofing, roofing and tunnel applications to protect surfaces from water penetration and which, after hardening, fully and permanently bonds with concrete and other cementitious compositions poured over the sealing device, as well as to provide an adhesive commonly used in the construction industry.

[0010] Another object of the present invention is to provide a seal that develops high early adhesion strength to concrete and other cementitious compositions poured on the seal surface after one day of hardening.

[0011] Surprisingly it has been found that a sealing device comprising a barrier layer and a functional layer based on a highly filled thermoplastic polymer composition and having a high surface roughness provides, after hardening, a high early adhesion strength to concrete cast on the surface of the functional layer.

[0012] The subject matter of the invention is a sealing arrangement according to claim 1 .

[0013] One of the advantages of the sealing device of the invention is that the formwork can be removed after 24 hours of hardening without the risk of the sealing device detaching from the vertical surface of the poured concrete body.

[0014] Another advantage of the seal of the present invention is that the improved surface roughness can be achieved by using a prior art foam extrusion process, which is easy to implement and does not significantly increase the production cost of the seal compared to prior art seals produced by coextrusion without the use of foaming gas.

[0015] Further subject-matter of the invention is presented in the other independent claims. Preferred aspects of the invention are presented in the dependent claims.

[0016] BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A cross section of a sealing device (1) according to the invention is shown, comprising a functional layer (2) having a first and a second major surface and a barrier layer (3) directly connected to the second major surface of the functional layer (2).

[0018] Figure 2 A cross section of a sealing device (1) according to the present invention is shown, comprising a first functional layer (2), a second functional layer (2') and a barrier layer (3), wherein the first main surface of the barrier layer (3) is directly connected to the second main surface of the first functional layer (2) and the second main surface of the barrier layer (3) is directly connected to the first main surface of the second functional layer (2'). DETAILED DESCRIPTION OF THE INVENTION

[0020] The subject of the invention is a sealing device (1) comprising a functional layer (2) having a first main surface and a second main surface and a barrier layer (3) directly or indirectly connected to the second main surface of the functional layer (2), the functional layer (2) comprising:

[0021] a) 20-75 wt. %, preferably 25-70 wt. %, of at least one thermoplastic polymer P1 and

[0022] b) 25-80% by weight, preferably 30-75% by weight, of at least one solid filler F, all proportions being based on the total weight of the functional layer (2), wherein

[0023] The first main surface of the functional layer (2) has a waviness factor W of at least 0.0125 1 / mm, preferably at least 0.0135 1 / mm, more preferably at least 0.0145 1 / mm. f Characterizing the surface roughness, the waviness factor W f RMS roughness W as waviness Sq and the peak density of the waviness W Spd The product of is determined by the waviness parameter W Sq and W Spd According to ISO 25178, the cut-off length λ is used c The waviness curve was determined by measuring the cross-sectional curve of 0.8 mm.

[0024] The term "polymer" refers to a chemically uniform collection of macromolecules resulting from a polymerization reaction (polymerization, polyaddition, polycondensation), wherein the macromolecules differ in their degree of polymerization, molecular weight and chain length. The term also encompasses derivatives of said collection of macromolecules resulting from a polymerization reaction, i.e. compounds obtained by reaction of functional groups in a predetermined macromolecule, such as addition or substitution, which may be chemically uniform or chemically inhomogeneous.

[0025] The term "thermoplastic" refers to any polymeric material that can be melted and resolidified with little or no change in physical properties.

[0026] The term "molecular weight" refers to the molar mass (g / mol) of a molecule or a portion of a molecule (also referred to as a "moiety"). The term "average molecular weight" refers to the number average molecular weight (M) of a mixture of oligomers or polymers of a molecule or moiety. n The molecular weight can be determined by conventional methods, preferably by gel permeation chromatography (GPC) using polystyrene as standard, styrene-divinylbenzene gel with porosities of 100 angstroms, 1000 angstroms and 10000 angstroms as column and tetrahydrofuran as solvent at a temperature of 35°C.

[0027] The term "glass transition temperature" (T g ) refers to the temperature above which the polymer component becomes soft and flexible, and below which the polymer component becomes hard and glassy. g ) is preferably determined by dynamic mechanical analysis (DMA) as the peak of the loss modulus (G") curve measured using an applied frequency of 1 Hz and a strain level of 0.1%.

[0028] The term "softening point" refers to the temperature at which a compound softens to a rubbery state or the temperature at which a crystalline part in a compound melts. The softening point can be determined by the ring and ball method according to the DIN EN 1238 standard.

[0029] The term "melting temperature" refers to the temperature at which a material undergoes a transition from a solid state to a liquid state. The melting temperature (T ) is preferably determined by differential scanning calorimetry (DSC) according to ISO 11357 standard using a heating rate of 2°C / min. m ). The measurements can be performed using a Mettler Toledo DSC 3+ apparatus and T m The value can be determined from the measured DSC curve with the aid of DSC software. If the measured DSC curve shows several peak temperatures, the first peak temperature from the lower temperature side in the thermogram is taken as the melting temperature (T m ).

[0030] The "amount or content of at least one component X" in the composition, e.g. the "amount of at least one thermoplastic polymer P1", refers to the sum of the individual amounts of all thermoplastic polymers P1 contained in the composition. For example, if the composition comprises 20% by weight of at least one thermoplastic polymer P1, the sum of the amounts of all thermoplastic polymers P1 contained in the composition is equal to 20% by weight.

[0031] The term "normal room temperature" refers to a temperature of 23°C.

[0032] The functional layer and the barrier layer are preferably sheet-like elements having a length and a width at least 5 times, preferably at least 25 times, more preferably at least 50 times the maximum thickness of the element. The term "major surface" in the present disclosure refers to the top and bottom surfaces of a sheet-like element, which define the thickness of the element between them.

[0033] In waterproofing applications, one of the most important properties is the adhesion strength by which the membrane is bonded to the substrate to be sealed, such as a concrete surface, thereby sealing against water penetration. If the adhesion strength is too low, gas is more likely to form between the membrane and the surface of the substrate, which can lead to a loss of watertightness.

[0034] It has been found that in pre-applied waterproofing applications, where the seal of the present invention is applied before forming the concrete structure to be waterproofed, the adhesion strength of the seal to the formed concrete structure can be significantly improved by increasing the surface roughness of the functional layer on which the fresh concrete is poured, in particular the early adhesion strength measured after 24 hours of hardening of the poured concrete.

[0035] The increased adhesion strength to concrete observed in pre-applied waterproofing applications is believed to result from the increased volume of pores and holes present on the outer exterior surface of the functional layer, which enables a relatively rapid formation of a mechanical bond between the functional layer and the poured concrete. It has also been discovered that a functional layer having a desired surface roughness can be readily obtained by using a foam extrusion process in which a molten polymer composition comprising the ingredients of the functional layer and a foaming gas is extruded through an extruder die. The foaming gas is released from the molten polymer composition upon discharge from the extruder die, wherein the functional layer first expands and its surface is eventually penetrated by the released foaming gas, resulting in the formation of pores and / or holes and other surface defects that can be characterized as the "surface roughness" of the functional layer.

[0036] The sealing device of the present invention comprises a functional layer having a first and a second main surface and a barrier layer connected indirectly or directly to the second main surface of the functional layer, wherein the first main surface of the functional layer has a surface roughness characterized by the following waviness parameter W f is at least 0.0125 1 / mm, preferably 0.0135 1 / mm, more preferably 0.0145 1 / mm, even more preferably 0.0155 1 / mm, and still more preferably 0.0165 1 / mm, wherein the waviness parameter W f Determined as the root mean square roughness W of the waviness Sq and the peak density of the waviness W Spd The product of , and where the waviness parameter W Sq and W Spd According to ISO 25178, the cut-off length λ is used c The waviness curve was determined for a measured cross-sectional curve of 0.8 mm.

[0037] RMS roughness of waviness W Sq and the peak density of the waviness W Spd is a normalized three-dimensional (3D) area parameter calculated from the waviness curve as defined in the ISO 25178 standard.

[0038] The term "waviness" is often used to refer to surface irregularities that have a significantly longer wavelength than the irregularities associated with the "roughness" of the surface. The 3D area parameters according to the ISO 25178 standard can be calculated based on the waviness curve or based on the roughness curve of the surface, where the 3D area parameters can be calculated from the measured cross-sectional curve of the surface using a suitable curve cut-off filter λ c and optional λ f Obtain the waviness curve.

[0039] The term "measured cross-sectional curve" refers in the present disclosure to the cross-sectional curve defined as "SF surface" in ISO 25178, which is obtained from the measured surface geometry (extracted surface) using the F-operator and optionally the S-filter. The surface geometry can be measured, for example, using a 3D scanner smartSCAN (trademark of AICON 3D Systems GmbH). In the case of the present invention, the cross-sectional curve of the first main surface of the functional layer is obtained by subtracting a second-order polynomial fitted with the measured data points from the measured surface geometry, and a cutoff length λ of 0.8 mm is used. c The waviness curve is obtained from the measured cross-sectional curve using preferably suitable computer software such as Premium (V7) software (trademark of DigitalSurf Corporation) was used to determine the cross-sectional curve, waviness curve and 3D area parameters according to ISO 25178 standard.

[0040] It has been found that a sealing device comprising a functional layer having a composition as defined in claim 1 and a surface roughness of the first major surface falling within the range presented above provides a high early adhesion strength measured after 24 hours of hardening of fresh concrete poured on the first major surface of the functional layer. In particular, it has been found that such a sealing device has an early adhesion strength that enables the use of the sealing device in pre-applied waterproofing applications, wherein the sealing device is positioned on a vertical surface of a formwork that is removed within 24 hours after pouring the concrete structure.

[0041] Furthermore, it was found that the sealing device exhibits an early concrete adhesion strength of at least 10 N / 50 mm, preferably at least 15 N / 50 mm, which is determined as the average peel resistance per unit width of the sealing device when peeling the sealing device from the surface of a concrete specimen, the concrete specimen being cast on the first main surface of the functional layer and hardened for 24 hours in a standard atmosphere (air temperature 23° C., relative air humidity 50%).

[0042] According to one or more embodiments, the functional layer comprises 25-65% by weight, preferably 30-60% by weight, more preferably 30-55% by weight of at least one thermoplastic polymer P1 and 35-75% by weight, preferably 40-75% by weight, more preferably 40-70% by weight of at least one solid filler F, all proportions based on the total weight of the functional layer.

[0043] According to one or more embodiments, the sum of the amounts of at least one thermoplastic polymer P1 and at least one solid filler F is at least 85 wt %, preferably at least 90 wt %, more preferably at least 92.5 wt %, even more preferably at least 95 wt %, based on the total weight of the functional layer.

[0044] The at least one solid filler F is preferably present in the functional layer as individual solid particles or aggregates of one or more solid particles dispersed in a continuous phase comprising at least one thermoplastic polymer P1. The expression "dispersed in a continuous phase" is understood to mean that the individual solid particles or aggregates of one or more particles are at least partially, preferably completely, surrounded by a continuous phase comprising at least one thermoplastic polymer. If the functional layer contains one or more inorganic binders, i.e. inorganic fillers, which undergo a hydration reaction in the presence of water, it is essential that these do not form a mutually crosslinked solid network of hydrated inorganic binders within the functional layer. Therefore, it can be preferred that the functional layer is substantially free of, more preferably completely free of, a mutually crosslinked solid network of hydrated inorganic binders at least before the sealing device is used for waterproofing of the substrate.

[0045] Preferably, at least one filler F has:

[0046] -d 98 The particle size is not greater than 750 μm, more preferably not greater than 500 μm, even more preferably not greater than 350 μm, still more preferably not greater than 250 μm and / or

[0047] -Median particle size d 50 not more than 350 μm, more preferably not more than 250 μm, even more preferably not more than 150 μm, still more preferably not more than 100 μm and / or

[0048] -d 10 The particle size is not greater than 100 μm, more preferably not greater than 75 μm, even more preferably not greater than 50 μm, still more preferably not greater than 25 μm.

[0049] The term "particle size" in this disclosure refers to the area equivalent spherical diameter (X 面积 ).

[0050] Term d 90 Particle size in this disclosure refers to the particle size below which less than 90% by volume of all particles are smaller than d 90 By analogy, the term "median particle size d 50 " refers to the particle size below which less than 50% by volume of all particles are smaller than d 50 value, and the term "d 10 The term "particle size" refers to the particle size below which less than 10% by volume of all particles are smaller than d 10 The particle size distribution can be measured by laser diffraction according to the method as described in standard ISO 13320:2009. For determining the particle size distribution, the particles are preferably suspended in water (wet dispersion method). A Mastersizer 2000 device (trademark of Malvern Instruments Ltd, GB) can be used in measuring the particle size distribution.

[0051] According to one or more embodiments, at least one solid filler F has a median particle size d 50 In the range of 0.1-150 μm, preferably 0.5-100 μm, more preferably 0.5-75 μm, even more preferably 1.0-50 μm, still more preferably 1.0-25 μm, most preferably 1.0-15 μm.

[0052] Preferably, the particles of at least one solid filler F are distributed throughout the entire volume of the functional layer. The term "distributed throughout" means that substantially all parts of the functional layer contain particles of at least one solid filler F, but does not necessarily mean that the distribution of the particles is completely uniform throughout the functional layer.

[0053] It may also be preferred that the functional layer comprises a homogeneously mixed mixture of at least one thermoplastic polymer P1 and at least one solid filler F. "Hygeneously mixed mixture" in the present disclosure refers to a composition in which the individual components are substantially uniformly distributed in the composition. A homogeneously mixed mixture of at least one thermoplastic polymer P1 and at least one solid filler F therefore refers to a composition in which particles of at least one solid filler F are uniformly / consistently distributed in a thermoplastic polymer phase comprising at least one thermoplastic polymer P1. It is clear to a person skilled in the art that within such a mixed composition there may be formed regions which have a slightly higher concentration of one or more components than other regions and that a 100% homogeneous distribution of all components is generally not achievable. However, such mixed compositions with an "imperfect" distribution of the components are also intended to be encompassed by the term "homogeneously mixed mixture" according to the present invention.

[0054] The type of at least one solid filler F is not particularly limited in the present invention. According to one or more embodiments, at least one solid filler F is selected from the group consisting of inert inorganic fillers, hydraulic binders, non-hydraulic binders, latent hydraulic binders, pozzolanic binders and synthetic organic fillers.

[0055] According to one or more embodiments, the at least one solid filler F comprises at least one inert inorganic filler F1. Generally, the expression "at least one component X comprises at least one component XN" such as "at least one solid filler F comprises at least one inert inorganic filler F1" is understood to mean in the context of the present disclosure that the functional layer comprises one or more inert inorganic fillers F1 as a representative of the at least one solid filler F.

[0056] The term "inert inorganic filler" refers to an inorganic filler which, unlike the hydraulic binder, does not undergo a hydrolysis reaction in the presence of water. Suitable inorganic fillers to be used as the at least one inert inorganic filler F1 include, for example, sand, granite, calcium carbonate, magnesium carbonate, clay, expanded clay, diatomaceous earth, pumice, mica, kaolin, talc, dolomite, xonotlite, perlite, vermiculite, wollastonite, barite, cristobalite, silicon dioxide, fumed silica, glass beads, hollow glass spheres, ceramic spheres, bauxite, crushed concrete and zeolite.

[0057] The term "sand" in this document refers to inorganic clastic sediments (clastic rocks), which are loose aggregates of small rounded or angular fine particles (loose sediments), which are separated from the original fine-grained structure during mechanical and chemical degradation and transported to their deposition site, said sediments having an SiO2 content of more than 50% by weight, in particular more than 75% by weight, particularly preferably more than 85% by weight. When used as an inert inorganic filler, the term "calcium carbonate" refers to a solid particulate material produced by grinding and / or precipitation of chalk, limestone or marble.

[0058] According to one or more embodiments, at least one inert inorganic filler is selected from the group consisting of sand, granite, calcium carbonate, magnesium carbonate, clay, expanded clay, diatomaceous earth, pumice, mica, kaolin, talc, potash, dolomite, xonotlite, perlite, vermiculite, wollastonite, barite, cristobalite, silicon dioxide (quartz), fumed silica, fused silica, bauxite, crushed concrete and zeolite, preferably selected from the group consisting of calcium carbonate, magnesium carbonate, diatomaceous earth, pumice, mica, talc, dolomite, xonotlite, perlite, vermiculite, wollastonite, barite and crushed concrete.

[0059] According to one or more embodiments, the at least one solid filler F comprises at least one hydraulic binder F2.

[0060] The term "hydraulic binder" refers to substances that react with water in a hydrolysis reaction with the formation of a solid inorganic hydrate or hydrate phase, which are insoluble in water or have a low water solubility. Thus, hydraulic binders such as Portland cement can harden and retain their strength when exposed to water, such as underwater or under high humidity conditions. In contrast, the term "non-hydraulic binder" refers to substances that harden by reaction with carbon dioxide and therefore do not harden in humid conditions or underwater.

[0061] Examples of suitable hydraulic binders to be used as the at least one hydraulic binder include hydraulic cement and hydraulic lime.The term "hydraulic cement" herein refers to a mixture of silicates and oxides including tricalcium silicate, belite, tricalcium aluminate and ferrous iron ore.

[0062] Commercially available hydraulic cements can be divided into five main cement types according to DIN EN 197-1, namely Portland cement (CEM I), Portland composite cement (CEM I I), blast furnace cement (CEM III), pozzolanic cement (CEM IV) and composite cement (CEM V). These five main types of hydraulic cements are further subdivided into an additional 27 cement types, which are known to the person skilled in the art and are listed in DIN EN 197-1. Naturally, all other hydraulic cements produced according to another standard, for example according to the ASTM standard or the Indian standard, are also suitable for use as the at least one hydraulic binder F2.

[0063] According to one or more embodiments, the at least one solid filler F comprises at least one non-hydraulic binder F3.

[0064] Examples of suitable non-hydraulic binders to be used as the at least one non-hydraulic binder F3 include efflorescent lime (non-hydraulic lime) and gypsum. The term "gypsum" in the present disclosure refers to any known form of gypsum, in particular calcium sulfate dehydrate, calcium sulfate alpha-hemihydrate, calcium sulfate beta-hemihydrate or calcium sulfate anhydrite or mixtures thereof.

[0065] According to one or more embodiments, the at least one solid filler F comprises at least one latent hydraulic binder F4.

[0066] The term "latent hydraulic binder" in the present disclosure refers to type II concrete additives having "latent hydraulic properties" as defined in the DIN EN 206-1:2000 standard. These types of inorganic binders are calcium aluminosilicates that are not able to harden directly or harden too slowly when mixed with water. The hardening process is accelerated in the presence of alkaline activators, which break the chemical bonds in the amorphous (or glassy) phase of the binder and promote the dissolution of ionic species and the formation of a calcium aluminosilicate hydrate phase.

[0067] Examples of suitable latent hydraulic binders to be used as at least one latent hydraulic binder F4 include ground granulated blast furnace slag. Ground granulated blast furnace slag is generally obtained by quenching molten iron slag from a blast furnace in water or steam to form a glassy pelletized product, followed by drying and grinding the glassy product into a fine powder.

[0068] According to one or more embodiments, the at least one solid filler F comprises at least one pozzolanic binder F5.

[0069] The term "pozzolanic binder" in the present disclosure refers to type II concrete additives having "pozzolanic properties" as defined in the DIN EN 206-1: 2000 standard. These types of inorganic binders are siliceous or aluminosilicate compounds which react with water and calcium hydroxide to form calcium silicate hydrates or calcium aluminosilicate hydrate phases.

[0070] Examples of suitable pozzolanic binders to be used as at least one pozzolanic binder F5 include natural pozzolanic ashes such as trass and artificial pozzolanic ashes such as fly ash and silica fume. The term "fly ash" in the present disclosure refers to the finely divided ash residue produced by the combustion of coal powder, which is carried away by the gases discharged from the furnace burning coal. The term "silica fume" in the present disclosure refers to finely particulate silicon in amorphous form. Silica fume is usually obtained as a by-product of the treatment of silicon ores such as quartz smelting in a silicon furnace, which leads to the formation of silicon monoxide gas, and the silicon monoxide gas is further oxidized when exposed to air to produce small particles of amorphous silicon dioxide.

[0071] According to one or more embodiments, the at least one solid filler F comprises at least one synthetic organic filler F6.

[0072] Suitable synthetic organic materials to be used as at least one synthetic organic filler F6 include in particular those having a melting point (T m ) is a plastic material with a temperature equal to or higher than 250° C., preferably equal to or higher than 275° C., such as polyamide, aromatic polyamide, epoxide, polystyrene, expanded polystyrene, polyethylene terephthalate (PET), poly(phenylene ether), polysulfone and polyethersulfone.

[0073] According to one or more embodiments, the at least one solid filler F comprises or consists of at least one inert inorganic filler F1 and / or at least one hydraulic binder F2, the at least one inert inorganic filler F1 being preferably chosen from: calcium carbonate, magnesium carbonate, diatomaceous earth, pumice, dolomite, xonotlite, perlite, barite and crushed concrete, more preferably chosen from: calcium carbonate and magnesium carbonate, and the at least one hydraulic binder F2 being preferably chosen from: Portland cement (CEM I), Portland composite cement (CEM I I), blast furnace cement (CEM III), pozzolanic cement (CEM IV) and composite cement (CEM V).

[0074] The type of the at least one thermoplastic polymer P1 is not particularly limited in the present invention.

[0075] According to one or more embodiments, at least one thermoplastic polymer P1 has:

[0076] - Melting temperature (T) determined by DSC according to ISO 11357 m ) in the range of 55-250°C, preferably 60-200°C, more preferably 65-175°C, even more preferably 70-165°C, still more preferably 75-155°C and / or

[0077] - a melt flow rate, measured according to ISO 1133 (190°C / 2.16 kg), of not more than 250 g / 10 min, preferably not more than 150 g / 10 min, more preferably not more than 100 g / 10 min, even more preferably not more than 50 g / 10 min, still more preferably not more than 25 g / 10 min and / or

[0078] -Glass transition temperature (T g ) is equal to or lower than 0°C, preferably equal to or lower than -10°C, more preferably equal to or lower than -20°C, even more preferably equal to or lower than -25°C, yet more preferably equal to or lower than -30°C, as determined by dynamic mechanical analysis (DMA), as the peak and / or

[0079] The flexural modulus at -23°C, measured according to ISO 178 standard, is not more than 700 MPa, preferably not more than 500 MPa, more preferably not more than 350 MPa, even more preferably not more than 250 MPa, still more preferably not more than 150 MPa, most preferably not more than 100 MPa.

[0080] Suitable polymers to be used as the at least one thermoplastic polymer P1 include, for example, ethylene-vinyl acetate copolymers (EVA), ethylene-acrylate copolymers, ethylene-α-olefin copolymers, ethylene-propylene copolymers, propylene-α-olefin copolymers, propylene-ethylene copolymers, polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polystyrene (PS), polyamide (PA), chlorosulfonated polyethylene (CSPE), ethylene propylene diene monomer rubber (EPDM) and polyisobutylene (PIB).

[0081] According to one or more embodiments, at least one thermoplastic polymer P1 is selected from the following: low-density polyethylene, linear low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylate copolymer, ethylene-α-olefin copolymer, ethylene-propylene copolymer, propylene-α-olefin copolymer, propylene-ethylene copolymer and polypropylene (PP), preferably selected from the following: low-density polyethylene, linear low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer and ethylene-propylene copolymer.

[0082] According to one or more embodiments, the at least one thermoplastic polymer comprises at least one ethylene vinyl acetate copolymer P11 and at least one thermoplastic polymer P12 that is not an ethylene vinyl acetate copolymer, which is preferably selected from low density polyethylene, linear low density polyethylene, high density polyethylene, ethylene-α-olefin copolymers and ethylene-propylene copolymers.

[0083] According to one or more embodiments, the amount ratio of at least one ethylene vinyl acetate copolymer P11 and at least one thermoplastic polymer P12 that is not an ethylene vinyl acetate copolymer is in the range of 5:1-1:5, preferably 3:1-1:3, more preferably 3:1-1:3.

[0084] According to one or more embodiments, the functional layer further comprises at least one surfactant SF. The term "surfactant" refers to a substance that reduces surface tension, which is generally an organic compound containing both hydrophobic and hydrophilic groups. Surfactants are generally classified as anionic, cationic, amphoteric, nonionic and polymeric surfactants based on the charge of their hydrophilic groups. Without being bound by any theory, the presence of the surfactant in the functional layer can reduce the surface tension of water contained in the fresh concrete poured on the functional layer, which can further enhance the ability of the fresh concrete to enter the holes and pores present on the first major surface of the functional layer.

[0085] Examples of suitable anionic surfactants to be used as at least one surfactant SF include, for example, surfactants containing carboxylate, sulfate, phosphate or sulfonate groups, such as amino acid derivatives; fatty alcohol ether sulfates; fatty alcohol sulfates; soaps; alkylphenol ethoxylates; fatty alcohol ethoxylates; alkane sulfonates; olefin sulfonates; and alkyl phosphates.

[0086] Examples of suitable cationic surfactants to be used as the at least one surfactant SF include, for example, quaternary ammonium or phosphorus compounds such as tetraalkylammonium salts, N,N-dialkylimidazoline compounds, dimethyldistearylammonium compounds, N-alkylpyridinium compounds and ammonium chloride.

[0087] Amphoteric (zwitterionic) surfactants have a cationic and anionic center attached to the same molecule. Examples of suitable amphoteric surfactants to be used as at least one surfactant SF include, for example, ampholytes such as aminocarboxylic acids and betaines.

[0088] Examples of suitable nonionic surfactants to be used as at least one surfactant SF include, for example, ethoxylates, for example ethoxylated adducts of alcohols, for example polyoxyalkylene polyols; amines; fatty acids; fatty acid amides; alkylphenols; ethanolamides; fatty amines; polysiloxanes; fatty acid esters; alkyl or alkylphenyl polyglycol ethers, for example fatty alcohol polyglycol ethers; alkyl glycosides; sugar esters; sorbitan esters; polysorbates or trialkylamine oxides; esters and amides of poly(meth)acrylic acid with polyalkylene glycols or aminopolyalkylene glycols, which may carry an alkyl group at up to one end.

[0089] Polymeric surfactants can be divided into two groups of compounds. The first group includes comb-type or rake-type polymers, in which there are organic polymer chains with hydrophobic groups at regular intervals along the chain and hydrophilic groups at random or regular intervals along the chain. The second group of polymeric surfactants includes block copolymers, in which there are blocks (B) of hydrophobic groups and blocks (A) of hydrophilic groups, usually in an ABA configuration. Certain polymeric surfactants such as ethylene oxide-propylene oxide copolymer surfactants can also be classified as nonionic surfactants.

[0090] According to one or more embodiments, at least one surfactant SF is selected from the group consisting of glyceryl monostearate, polycarboxylate ethers, polyether-modified polysiloxanes, polyalkylene oxide siloxanes, hydroxyethylamines, erucamide, stearyl stearamide, alkali metal alkane sulfonates, and alkyl aryl sulfonates.

[0091] Suitable glyceryl monostearate is commercially available, for example as HP (from Danisco) is a trade name for HP.

[0092] Suitable polycarboxylate ethers include polycarboxylate ether-based superplasticizers (PCEs) consisting of methoxy-polyethylene glycol copolymers (side chains) grafted to methacrylic acid copolymers (backbone). Suitable polycarboxylate ether-based superplasticizers are commercially available, for example as Polymer PC-2, Polymer RMC-2, 125P and R-750MC (from Sika AG) is a trade name for R-750MC.

[0093] Suitable polyether-modified polysiloxanes include polyether polysiloxane copolymers, which are commercially available, for example, as B8870 (trade name from Evonik Industries).

[0094] Suitable polyalkylene oxide siloxanes are commercially available, for example as L-1500 (trade name from Momentive).

[0095] Examples of suitable hydroxyethylamines include bis(2-hydroxyethyl)amine, which is commercially available, for example, as 300 (from Akzo Nobel) trade name.

[0096] Suitable erucamide and stearyl stearamide are commercially available, for example as E180 and S180 (from PMC Biogenix).

[0097] Examples of suitable alkali metal alkanesulfonates include sodium alkanesulfonate, which is commercially available, for example, as 3002 (from Akzo Nobel) and 93P (from Emery Oleochemicals).

[0098] Suitable alkylaryl sulfonates are commercially available, for example as For example 2300, 3100 and A trade name for 3700 (from Airproducts).

[0099] If present in the functional layer, the at least one surfactant SF preferably accounts for at least 0.01 wt.-%, more preferably at least 0.05 wt.-%, even more preferably at least 0.1 wt.-%, based on the total weight of the functional layer. It is also preferred that the amount of at least one surfactant SF in the functional layer is not more than 10 wt.-%, more preferably not more than 5 wt.-%, even more preferably not more than 3.5 wt.-%, based on the total weight of the functional layer.

[0100] According to one or more embodiments, at least one surfactant SF accounts for 0.05-7.5 wt %, preferably 0.1-5.0 wt %, more preferably 0.25-3.5 wt %, even more preferably 0.5-3.0 wt %, and even more preferably 0.5-2.5 wt % of the total weight of the functional layer.

[0101] Due to the asymmetric surface structure present in the first main surface of the functional layer, the thickness of the functional layer usually varies along the length and width of the sealing device. Some holes and holes in the functional layer can even reach the first main surface of the barrier layer, in which case the thickness of the functional layer measured at such a specific position may not even be measurable. However, it may be preferred that the functional layer has a maximum thickness of not more than 25 mm, preferably not more than 15 mm, more preferably not more than 10 mm, even more preferably not more than 5 mm, and even more preferably not more than 2.5 mm. In the context of the present invention, the maximum thickness of the functional layer can be determined according to the DIN EN 1849-2 standard using an optical microscope, for example a Keyence VHX-600 with a magnification of 30 times.

[0102] In addition to the surface roughness of the first major surface of the functional layer, it has also been found that the mass per unit area of ​​the functional layer also affects the early adhesion strength obtained by the sealing device in the pre-applied waterproofing application. It may therefore be preferred that the functional layer has a mass per unit area of ​​at least 100 g / m 2 , more preferably at least 150 g / m 2 , even more preferably at least 200 g / m 2 According to one or more embodiments, the functional layer has a mass per unit weight of 100-1500 g / m 2 , preferably 150–1250g / m 2 , more preferably 250-1000g / m 2 , even more preferably 350-1000 g / m 2 , and more preferably 450-1000g / m 2 , most preferably 500–1000g / m 2 within the range.

[0103] The functional layer may also contain one or more additives such as UV and heat stabilizers, antioxidants, plasticizers, flame retardants, dyes, pigments such as titanium dioxide and carbon black, matting agents, antistatic agents, impact modifiers, biocides, and processing aids such as lubricants, slip agents, antiblocking agents and demoulding aids. It is preferred that the total amount of these types of additives is no more than 10% by weight, preferably no more than 5% by weight, based on the total weight of the functional layer.

[0104] The sealing device further comprises a barrier layer which is directly or indirectly connected to the second major surface of the functional layer.

[0105] The functional layer and the barrier layer may be connected to each other indirectly, for example, via a connecting layer such as an adhesive layer or via a fiber-based layer or a combination thereof. In the case of a porous connecting layer such as an open weave fabric, the functional layer may be connected partly directly and partly indirectly to the barrier layer.

[0106] The expression "direct connection" is understood to mean in the context of the present invention that there are no further layers or substances between the layers, and the opposing surfaces of the two layers are directly bonded to each other or adhere to each other. In the transition region between the two layers, the materials forming the layers may also be present mixed with each other.

[0107] According to one or more embodiments, the barrier layer has a first and a second major surface, wherein at least a portion of the first major surface of the barrier layer is directly connected to the second major surface of the functional layer. According to one or more embodiments, at least 50%, preferably at least 75% by weight, and more preferably at least 95% of the area of ​​the barrier layer is directly connected to the second major surface of the functional layer.

[0108] The composition of the barrier layer is not particularly limited. However, the barrier layer should be as water-resistant as possible and should not decompose or become mechanically damaged even under the prolonged influence of water or moisture.

[0109] It is further preferred that the barrier layer is in the form of a flexible plastic layer. This allows the sealing device to be wound into a roll, typically during production, and then easily applied to the surface of the substrate to be waterproofed. Preferably, the barrier layer has a tensile modulus of elasticity measured according to EN ISO 527-3 of not more than 500 MPa, preferably not more than 350 MPa, more preferably not more than 250 MPa, even more preferably not more than 150 MPa, yet more preferably not more than 100 MPa.

[0110] According to one or more embodiments, the barrier layer comprises at least 50 wt.-%, preferably at least 65 wt.-%, more preferably at least 75 wt.-%, even more preferably at least 85 wt.-%, even more preferably at least 90 wt.-%, still more preferably at least 95 wt.-% of at least one thermoplastic polymer P2.

[0111] According to one or more embodiments, at least one thermoplastic polymer P2 has:

[0112] - Melting temperature (T) determined by DSC according to ISO 11357 m ) in the range of 55-250°C, preferably 60-200°C, more preferably 65-175°C, even more preferably 70-165°C, still more preferably 75-155°C and / or

[0113] - a melt flow rate, measured according to ISO 1133 (190°C / 2.16 kg), of not more than 250 g / 10 min, preferably not more than 150 g / 10 min, more preferably not more than 100 g / 10 min, even more preferably not more than 50 g / 10 min, still more preferably not more than 25 g / 10 min and / or

[0114] -Glass transition temperature (T g) is equal to or lower than 0°C, preferably equal to or lower than -10°C, more preferably equal to or lower than -20°C, even more preferably equal to or lower than -25°C, yet more preferably equal to or lower than -30°C, as determined by dynamic mechanical analysis (DMA), as the peak and / or

[0115] The flexural modulus at -23°C, measured according to ISO 178 standard, is not more than 700 MPa, preferably not more than 500 MPa, more preferably not more than 350 MPa, even more preferably not more than 250 MPa, still more preferably not more than 150 MPa, most preferably not more than 100 MPa.

[0116] Suitable polymers to be used as at least one thermoplastic polymer P2 include, for example, ethylene-vinyl acetate copolymers (EVA), ethylene-acrylate copolymers, ethylene-α-olefin copolymers, ethylene-propylene copolymers, propylene-α-olefin copolymers, propylene-ethylene copolymers, polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polystyrene (PS), polyamide (PA), chlorosulfonated polyethylene (CSPE), ethylene propylene diene monomer rubber (EPDM) and polyisobutylene (PIB).

[0117] According to one or more embodiments, at least one thermoplastic polymer P2 is selected from the following: low-density polyethylene, linear low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylate copolymer, ethylene-α-olefin copolymer, ethylene-propylene copolymer, propylene-α-olefin copolymer, propylene-ethylene copolymer and polypropylene (PP), preferably selected from the following: low-density polyethylene, linear low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer and ethylene-propylene copolymer.

[0118] It may be preferred that the at least one thermoplastic polymer P2 contained in the barrier layer is miscible with the at least one thermoplastic polymer P1 contained in the functional layer. The polymers are "miscible" in the present disclosure means that the polymer blend consisting of at least one thermoplastic polymer P1 and at least one thermoplastic polymer P2 has a negative Giggs free energy and a heat of mixing. Polymer blends consisting of completely miscible polymer components tend to have a single glass transition temperature (T g ).

[0119] In addition to the at least one thermoplastic polymer P2, the barrier layer may also contain one or more additives such as UV and heat stabilizers, antioxidants, plasticizers, fillers, flame retardants, dyes, pigments such as titanium dioxide and carbon black, matting agents, antistatic agents, impact modifiers, biocides, and processing aids such as lubricants, slip agents, antiblocking agents and demoulding aids. However, it is preferred that the total amount of these types of additives is not more than 45% by weight, preferably not more than 35% by weight, more preferably not more than 25% by weight, even more preferably not more than 15% by weight, based on the total weight of the barrier layer.

[0120] The thickness of the barrier layer is not subject to any particular restrictions. However, sealing devices comprising a barrier layer having a thickness greater than 10 mm or less than 0.1 mm are generally not practical in waterproof applications. Preferably, the barrier layer has a thickness of at least 0.1 mm, more preferably at least 0.25 mm. According to one or more embodiments, the barrier layer has a thickness of 0.1-10.0 mm, preferably 0.25-5.0 mm, more preferably 0.3-3.5 mm, even more preferably 0.35-2.5 mm. The thickness of the barrier layer can be determined by using a measurement method as defined in the DIN EN 1849-2 standard.

[0121] The sealing device of the present invention can be provided in the form of a prefabricated product that is delivered to the construction site in the form of a roll, which is then unrolled and cut to provide a sheet having a length that exceeds the width of the sheet. The terms "width" and "length" refer to two perpendicular dimensions measured in the horizontal plane of the top and bottom surfaces of the sheet. Generally, the "width" of a sheet is the smaller of the horizontal dimensions of the sheet. Therefore, the "width" of a sealing device refers to the smaller dimension measured in the horizontal plane of the barrier layer in a direction perpendicular to the length of the barrier layer.

[0122] Preferably, the sealing device has a width of no more than 10 m, more preferably no more than 5 m. According to one or more embodiments, the sealing device has a width in the range of 0.5-5 m, preferably 0.75-4 m, more preferably 0.85-3.5 m, even more preferably 1.0-3 m. According to one or more further embodiments, the sealing device has a width in the range of 0.05-1 m, preferably 0.1-0.85 m, more preferably 0.15-0.65 m, even more preferably 0.15-0.5 m.

[0123] Especially if the sealing device is used for waterproofing of roof substrates, it may be preferred that the barrier layer comprises one or more reinforcing layers, which serve to improve the dimensional stability of the barrier layer. However, it may or even be preferred that the barrier layer does not contain such reinforcing layers, especially if the sealing device is used for waterproofing of underground structures.

[0124] If used, the reinforcing layer may be at least partially embedded, preferably completely embedded, in the barrier layer. The expression "at least partially embedded" means that the reinforcing layer is at least partially covered by the matrix of the barrier layer. The type of reinforcing layer is not particularly limited. For example, reinforcing layers commonly used to improve the dimensional stability of thermoplastic waterproofing and roofing membranes may be used. Preferably, the reinforcing layer comprises at least one layer of fibrous material, preferably selected from nonwoven fabrics, woven fabrics and nonwoven scrims, more preferably selected from nonwoven fabrics and nonwoven scrims.

[0125] The term "nonwoven fabric" in the present disclosure refers to a material composed of fibers that are bonded together using chemical, mechanical or thermal bonding methods and which is neither woven nor knitted. Nonwoven fabrics can be produced, for example, by using carding or needle punching, in which the fibers are mechanically entangled to obtain the nonwoven fabric. In chemical bonding, a chemical binder such as an adhesive material is used to hold the fibers together in the nonwoven fabric.

[0126] The term "nonwoven scrim" in the present disclosure refers to a web-like nonwoven product consisting of yarns that are stacked and chemically bonded to each other. Typical materials for nonwoven scrims include metal, fiberglass and plastics, particularly polyester, polypropylene, polyethylene and polyethylene terephthalate (PET).

[0127] According to one or more embodiments, the sealing device further comprises a second functional layer (2') having a first and a second major surface, wherein the second major surface of the barrier layer (3) is directly or indirectly connected to the first major surface of the second functional layer (2'), and wherein the second functional layer (2') comprises:

[0128] a) 20-75 wt. %, preferably 25-70 wt. %, of at least one thermoplastic polymer P1 and

[0129] b) 25-80% by weight, preferably 30-75% by weight, of at least one solid filler F, all proportions being based on the total weight of the second functional layer ( 2 ′).

[0130] According to one or more embodiments, the second major surface of the second functional layer has a waviness factor W of at least 0.0125 1 / mm, preferably at least 0.0135 1 / mm, more preferably at least 0.0145 1 / mm. f Characterize the surface roughness, waviness factor W f RMS roughness W as waviness Sq and the peak density of the waviness W Spd The product of is determined by the waviness parameter W Sq and W Spd According to ISO 25178, the cut-off length λ is used c The waviness curve was determined for a measured cross-sectional curve of 0.8 mm.

[0131] The preferences stated above for the functional layer, the barrier layer, the at least one thermoplastic polymer P1, the at least one solid filler F and the at least one surfactant SF apply equally to all other subjects of the present invention, unless otherwise stated.

[0132] Another subject of the present invention is a method for producing a sealing device, which comprises the step of extruding or co-extruding a first molten polymer composition comprising the ingredients of the functional layer as defined above through an extruder die, wherein the first molten polymer composition also contains a foaming gas, which is released from the first molten polymer composition through the surface of the functional layer discharged from the extruder die.

[0133] After the molten polymer composition is discharged from the extruder die, the functional layer first expands due to the volume increase of the foaming gas, which leads to the formation of closed-cell structures in the functional layer material. Eventually, the surface of the functional layer is penetrated by the foaming gas, which leads to the formation of open or semi-open bubbles, holes, holes and other surface defects that can be entered from the first major surface side of the functional layer. The distribution and size of these surface structures that can be entered from the first major surface side of the functional layer can be characterized using the 3D-surface roughness parameters as discussed above.

[0134] In order to prevent premature release of the foaming gas from the molten polymer composition, ie, before the molten polymer composition is discharged through the extruder die, the extruder should be operated using closed venting unit(s).

[0135] The first molten polymer composition is preferably obtained by melt processing a first starting composition comprising the ingredients of the functional layer. Melt processing is preferably performed using an extruder such as a single or twin screw extruder or a planetary roll extruder.

[0136] The foaming gas released from the first molten polymer composition through the surface of the functional layer is preferably present in the first starting composition or the first molten polymer composition in the form of a physical or chemical foaming agent. If it is a chemical foaming agent, the foaming agent is preferably added to the first starting composition and the foaming gas is generated during the melt processing of the first starting composition. If it is a physical foaming agent, the foaming agent is preferably added to the first starting composition or the melt-processed starting composition before the first molten polymer composition is extruded through the extruder die.

[0137] Suitable physical foaming agents to be used in the method for producing the sealing device include gaseous and liquid physical foaming agents. Gaseous physical foaming agents such as compressed nitrogen or carbon dioxide can be directly injected into the melt-processed starting composition under high pressure, which is transported by melt processing equipment such as an extruder barrel. Liquid physical foaming agents include volatile liquids that produce gases by evaporation. Suitable liquid physical foaming agents generally include water, short-chain aliphatic hydrocarbons, for example, having five to seven carbon atoms, and their halogenated, especially chlorinated and fluorinated derivatives. Particularly suitable liquid physical foaming agents have a standard boiling point measured at a pressure of 1 bar of not more than 250°C, preferably not more than 200°C. The standard boiling point of the liquid physical foaming agent can be measured using an ebulliometer.

[0138] Chemical blowing agents (also called foaming agents) are generally solids that release gas(es) by means of a chemical reaction, such as decomposition, when exposed to elevated temperatures. Chemical blowing agents can be either inorganic or organic.

[0139] According to one or more embodiments, the first molten polymer composition is obtained by melt processing a first starting composition comprising the ingredients of the functional layer and additionally at least one chemical blowing agent CBA.

[0140] According to one or more embodiments, at least one chemical blowing agent CBA has a maximum decomposition peak temperature measured by differential scanning calorimetry (DSC) in the range of 85-225° C., preferably 95-215° C., more preferably 105-205° C., and even more preferably 115-195° C. Preferably, the maximum decomposition peak measured by DSC is determined by a DSC822e differential scanning calorimeter from Mettler-Toledo, by keeping the sample at 25° C. for 2 min, then heating the sample from 25° C. to 280° C. at a rate of 5° C. / min, then keeping the sample at 280° C. for 2 min, and finally cooling the sample from 280° C. to 25° C. at a rate of 10° C. / min.

[0141] Suitable substances to be used as at least one chemical blowing agent CBA include, for example, azodicarbonamide, azobisisobutyronitrile, azocyclohexanecarbonitrile, dinitrosopentamethylenetetramine, azodiaminobenzene, calcium azide, 4,4′-diphenyldisulfonyl azide, benzenesulfonylhydrazide, 4,4-oxybenzenesulfonylsemicarbazide, 4,4-oxybis(benzenesulfonylhydrazide), diphenylsulfone-3,3-disulfonylhydrazide, p-toluenesulfonylhydrazide, p-toluenesulfonylsemicarbazide, trihydrazinotriazine, N,N′-dimethyl-N,N′-dinitrosoterephthalamide, diazoaminobenzene, diazoaminotoluene, hydrazonodicarbonamide, barium azodicarboxylate, 5-hydroxytetrazole, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate, potassium bicarbonate and organic acids.

[0142] Most of the preferred chemical blowing agents listed above, such as sodium bicarbonate, are solid at normal room temperature and are usually provided in powder form. The particle size of such powders is preferably not too low in order to prevent premature decomposition of the chemical blowing agent during the premixing process, such as during premixing of the ingredients of the first starting composition. A narrow particle size distribution may also be preferred in order to better control the decomposition temperature of the chemical blowing agent.

[0143] According to one or more embodiments, at least one chemical blowing agent CBA has a median particle size d 50 The solid particles are present in the first starting composition in the form of particles in the range of 0.5-100 μm, preferably 1.0-75 μm, more preferably 2.5-50 μm, even more preferably 5-35 μm.

[0144] Suitable organic acids for use as at least one chemical blowing agent CBA include, for example, monocarboxylic acids such as acetic acid and propionic acid, solid polycarboxylic acids such as solid, hydroxy-functional or unsaturated dicarboxylic acids, tricarboxylic acids, tetracarboxylic acids or polycarboxylic acids, in particular citric acid, tartaric acid, malic acid, fumaric acid and maleic acid.

[0145] Although some of the compounds used in the present invention are characterized as being useful for specific functions, it should be understood that the use of these compounds is not limited to their described functions. For example, it is also possible that some of the substances presented above as chemical blowing agents can also be used as activators for at least one chemical blowing agent CBA.

[0146] For example, commonly used activators for chemical blowing agents based on organic acids include bicarbonates (bicarbonates) and carbonates, particularly those having the formula XHCO3 or X2CO3, wherein X represents a general cation such as Na + , K + NH4 + 、1 / 2Zn 2+ 、1 / 2Mg 2+ and 1 / 2Ca 2+ , especially Na + and K + On the other hand, these types of activators may themselves be suitable for use as at least one chemical blowing agent CBA.

[0147] According to one or more embodiments, the first starting composition comprises, in addition to at least one chemical blowing agent CBA, at least one activator for at least one chemical blowing agent CBA.

[0148] According to one or more embodiments, at least one chemical blowing agent CBA is selected from bicarbonates of formula XHCO3 and carbonates of formula X2CO3, wherein X represents a general cation, in particular Na + , K +NH4 + 、1 / 2Zn 2+ 、1 / 2Mg 2+ or 1 / 2Ca 2+ , preferably selected from bicarbonates of XHCO3, wherein X represents a general cation, in particular Na + , K + NH4 + 、1 / 2Zn 2+ 、1 / 2Mg 2+ or 1 / 2Ca 2+ , more preferably selected from sodium bicarbonate and potassium bicarbonate.

[0149] The at least one chemical blowing agent CBA is preferably present in the first starting composition in an amount of not more than 10 wt.-%, more preferably not more than 7.5 wt.-%, even more preferably not more than 5 wt.-%, still more preferably not more than 3.5 wt.-%, most preferably not more than 2.0 wt.-%, based on the total weight of the first starting composition.

[0150] According to one or more embodiments, at least one chemical blowing agent CBA accounts for at least 0.1 wt %, preferably at least 0.15 wt %, more preferably at least 0.2 wt %, even more preferably at least 0.25 wt % of the total weight of the first starting composition. According to one or more additional embodiments, at least one chemical blowing agent CBA accounts for 0.1-3.0 wt %, preferably 0.15-2.5 wt %, more preferably 0.2-2.0 wt %, even more preferably 0.2-1.75 wt %, even more preferably 0.2-1.5 wt %, most preferably 0.25-1.25 wt % of the total weight of the first starting composition.

[0151] It was found that adding at least one chemical blowing agent CBA to the first starting composition in an amount falling within the above-recited range can provide the desired surface roughness of the functional layer. In addition, it was found that the use of at least one chemical blowing agent CBA in an amount greater than 2.0% by weight of the total amount of the first starting composition can in some cases lead to the formation of pores and holes extending between the outer surfaces of the functional layer. In some cases, it has been found that the use of an excess of at least one chemical blowing agent leads to the formation of pores and holes also in the barrier layer, which is then unable to perform its waterproofing function.

[0152] In particular, if the at least one solid filler F comprises a hydraulic binder, it may be preferred that the first starting composition contains only a small amount of water. According to one or more embodiments, the first starting composition comprises less than 10% by weight, preferably less than 7.5% by weight, more preferably less than 5% by weight, even more preferably less than 3.5% by weight of water.

[0153] The first molten polymer composition is preferably extruded or coextruded using an extrusion device comprising an extruder and a die.

[0154] Such extrusion equipment is well known to those skilled in the art. Suitable extruders include a barrel and a screw unit or plunger contained in the barrel. Any conventional extruder such as a plunger extruder, a single screw extruder or a twin screw extruder can be used. Preferably, the extruder is a screw extruder, more preferably a twin screw extruder. The screw unit of a conventional screw extruder is generally considered to include a feed section, a transition section and a metering section. In the feed section, the thermoplastic composition enters the channel of the rotating screw and is transported to the transition section, where the composition is compressed and melted. The composition should be completely melted when it leaves the transition section. The function of the metering section is to homogenize the molten composition and allow it to be metered or pumped out at a constant rate. The extrusion equipment also includes a die head, preferably a flat die head, which is composed of a manifold, a channel and a lip area. If it is a co-extrusion process, the extrusion equipment preferably includes at least two extruders, preferably a twin screw extruder and a single or multi-manifold die head.

[0155] The extruder barrel comprises a feed port for adding the material to be extruded to the extruder, and an output port for the material to leave the barrel. The output port is connected to the die head by a gate or adapter component. A mixing device may be between the barrel and the die head. The feed port is usually connected to a hopper for adding the material to be extruded. It is preferred that a screen assembly and a porous plate are placed at the end of the barrel to avoid obstruction in the nozzle. The extruder also comprises a heating element, a cooling element, a temperature sensor and a temperature control element to provide a temperature controlled area along the barrel, also referred to as a barrel zone. The extruder may comprise, for example, 3 to 8 barrel zones, preferably at least 5 barrel zones, and temperature distribution may be achieved in the barrel by using barrel zones.

[0156] Preferably, most, preferably the entire amount of at least one thermoplastic polymer P1 is added to the extruder through the feed opening. It may be preferred to add at least a portion of at least one solid filler F to the extruder through another port located downstream of the feed opening. The term "downstream" in this document refers to the direction to the output port. For example, it may be advantageous to add not more than 50% by weight, preferably not more than 30% by weight, more preferably not more than 10% by weight of the total amount of at least one solid filler F to the extruder together with the entire amount of at least one thermoplastic polymer P1 through the feed opening, and to add the remaining portion of at least one solid filler F to the extruder through another port located downstream of the feed opening.

[0157] It may also be preferred to introduce only a portion of the at least one chemical blowing agent CBA and / or the at least one surfactant SF (if used) into the extruder via a feed port and to introduce at least 10% by weight, preferably at least 20% by weight, of the total amount of these components into the extruder via another port located downstream of the feed port.

[0158] It is also possible to mix some or all of the ingredients of the first starting composition to obtain a premix, which is then added to the extruder through the feed port. Premixing can be performed using any type of conventional blending equipment known to those skilled in the art. In the premixing process, particles of at least one thermoplastic polymer P1 are mixed with other ingredients, for example with at least one solid filler F and / or with at least one chemical foaming agent CBA at an elevated temperature to obtain a uniformly mixed mixture. It is also possible to process some or all of the ingredients of the first starting composition into pellets or pellets in a compounding extruder, which are then added to the extruder through the feed port.

[0159] The preferred extrusion temperature depends on the embodiment of the sealing device, in particular on the type of polymer basis of the functional layer. The term "extrusion temperature" refers to the temperature of the extruded composition in the die outlet. According to one or more embodiments, the extrusion temperature is in the range of 80-250°C, preferably 100-240°C, more preferably 120-220°C, even more preferably 140-200°C.

[0160] The preferred extrusion pressure depends on the embodiment of the sealing device, in particular on the type of polymer basis of the functional layer and on the amount of at least one solid filler F in the functional layer. The term "extrusion pressure" refers to the pressure of the composition at the end of the metering zone just before the composition enters the die inlet.

[0161] According to one or more embodiments, the extrusion pressure is in the range of 20 - 350 bar, preferably 30 - 240 bar, more preferably 35 - 200 bar, even more preferably 40 - 130 bar.

[0162] The extrusion process may be performed by using different temperature profiles, such as an increasing temperature profile (where the temperature increases downstream of the barrel), a decreasing temperature profile (where the temperature decreases downstream of the barrel), and a hump-shaped temperature profile (where the temperature increases from the feed port toward a certain set point, such as toward the middle of the barrel). It may be preferred to perform the extrusion process by using a hump-shaped temperature profile.

[0163] Preferably, at least part, for example at least 5% by weight, in particular at least 10% by weight, preferably 25% by weight, more preferably at least 50% by weight, most preferably at least 75% by weight, of the at least one chemical blowing agent CBA decomposes while the first starting composition is conveyed through the barrel and before the melt-processed starting composition enters the die. This is ensured by selecting a suitable chemical blowing agent or a suitable mixture of chemical blowing agent and activator and by adjusting the temperature profile in the feed section, transition section and metering section. Preferably, the first starting composition is maintained at a temperature of at least 10° C. greater than the decomposition temperature of the at least one chemical blowing agent CBA while the first starting composition is conveyed through the extruder barrel.

[0164] Furthermore, the extruder is preferably operated using closed venting unit(s).It is essential that at least a majority of the foaming gas released inside the extruder barrel remains trapped in the melt processed polymer composition and is not released before the first molten polymer composition exits the extruder die.

[0165] According to one or more embodiments, the method of producing a sealing device comprises the additional step of extruding or co-extruding through an extruder die a second molten polymer composition comprising the ingredients of the barrier layer as defined above.

[0166] Preferably, the second molten polymer composition is obtained by melt processing a second starting composition comprising the ingredients of the barrier layer.

[0167] Further details of the method of producing the sealing device depend on the embodiment of the sealing device.

[0168] According to one or more embodiments, the method for producing the sealing device comprises coextruding a first molten polymer composition and a second molten polymer composition using a coextrusion device through a conventional extruder die, preferably a flat die. Preferably, the coextrusion device comprises a first extruder for melt processing the first starting composition and a second extruder for melt processing the second starting composition. The first and second molten polymer compositions are extruded through a conventional extruder die, and the extruder die can be equipped with a single or multiple manifolds. The thickness of the extruded functional layer and the barrier layer and the adhesion between the layers can be easily controlled by adjusting the die lip of the coextrusion device. Preferably, the first extruder is operated using a closed exhaust unit (one or more) to prevent premature release of the foaming gas.

[0169] It may be preferred that the method of producing the sealing device comprises the further step of employing spaced apart calendering chill rolls through which the composite article comprising the extruded functional layer and the extruded barrier layer is drawn after the coextrusion step. The thickness of the functional layer and the barrier layer may be further controlled by adjusting the gap size between the calendering chill rolls. Preferably, the gap between the calendering chill rolls is adjusted so that substantially no pressure is applied on the surface of the functional layer in order to obtain a functional layer having a desired surface roughness.

[0170] According to one or more additional embodiments, the method for producing the sealing device comprises extruding a first molten polymer composition through a first extruder die using a first extrusion device and extruding a second molten polymer composition through a second extruder die using a second extrusion device and bonding the functional layer and barrier layer thus obtained to each other. The extruded functional layer and barrier layer may be thermally laminated to each other or adhered to each other using an adhesive, for example. The term "thermal lamination" refers here to a method comprising partially melting at least one layer when applying thermal energy, followed by a cooling step, which results in a bond being formed between the layers without using an adhesive such as an adhesive.

[0171] According to one or more additional embodiments, the method of producing a sealing device comprises extruding a second molten polymer composition on a second major surface of a preformed functional layer through an extruder die or extruding a first molten polymer composition on a first major surface of a preformed barrier layer through an extruder die. In these embodiments, the barrier layer is formed and bonded simultaneously with the previously formed functional layer, or vice versa.

[0172] Another subject of the invention is a sealing device obtained by using the method for producing a sealing device according to the invention.

[0173] The sealing device may be a waterproof membrane, a roof membrane, a tunnel membrane or a sealing tape.

[0174] A further subject of the invention is the use of a sealing device according to the invention for waterproofing a substrate.The substrate to be waterproofed may be any structure or civil engineering structure which is to be sealed against moisture and water.

[0175] According to one or more embodiments, using a sealing device for waterproofing a substrate comprises the following steps:

[0176] i) applying the sealing device according to the invention to the surface of a substrate such that the second main surface of the barrier layer faces the surface of the substrate,

[0177] ii) pouring a fresh concrete composition onto the first major surface of the functional layer, and

[0178] iii) allowing the fresh concrete composition to harden.

[0179] The term "fresh concrete composition" refers to a concrete composition before hardening, in particular before the concrete composition sets. The poured concrete composition after hardening may be part of a structure, in particular an above-ground or underground structure, such as a building, a garage, a tunnel, a landfill, a reservoir, a pond, a dam or an element for use in a prefabricated building structure.

[0180] According to one or more additional embodiments, using the sealing device for waterproofing a substrate comprises the following steps:

[0181] i) providing a sealing device according to the invention,

[0182] ii) applying an adhesive layer on at least a portion of the surface of the substrate,

[0183] iii) contacting the adhesive layer to the first major surface of the functional layer.

[0184] The adhesive may be a fresh cementitious composition or a synthetic resin based adhesive composition, such as a reactive epoxy based, polyurethane based or acrylic based adhesive composition or a non-reactive thermoplastic based or rubber based adhesive composition.

[0185] The term "cement-based composition" refers to concrete, shotcrete, cement paste, mortar, mud or a combination thereof. The terms "mud", "mortar", "concrete", "shotcrete" and "cement paste" are terms well known in the prior art. Mud is a mixture comprising a hydraulic cement binder, typically a mixture of portland cement, masonry cement, mortar cement. Mortar is a mud that additionally includes fine aggregates such as sand. Concrete is a mortar that additionally includes coarse aggregates such as crushed gravel or stone. Shotcrete is concrete (or sometimes mortar) that is delivered through a hose and pneumatically sprayed at high speed onto a surface. Cement-based compositions can be formed by mixing the required amounts of certain components such as hydraulic cement, water and fine and / or coarse aggregates to produce a specific cement-based composition.

[0186] According to one or more additional embodiments, using the sealing device for waterproofing a substrate comprises the following steps:

[0187] i) providing a sealing device according to the invention,

[0188] ii) applying a layer of the adhesive composition on at least a portion of the surface of the substrate to form a first adhesive film and applying a layer of the adhesive composition on the first major surface of the functional layer to form a second adhesive film,

[0189] iii) contacting the first and second adhesive layers to achieve an adhesive bond between the substrate and the sealing device.

[0190] The adhesive composition used in these embodiments is preferably a solvent or water-based contact adhesive. Suitable solvent-based contact adhesives are commercially available, for example, as (Trade name of Sika AG). Example

[0191] The following compounds shown in Table 1 were used in the Examples:

[0192] Table 1

[0193]

[0194]

[0195] Preparation of sealing device

[0196] Exemplary seals Ex-1 to Ex-4 and reference seals Ref-1 and Ref-2 were produced using a laboratory-scale coextrusion apparatus comprising two twin-screw extruders (Berstorff GmbH), a flat die and a set of water-cooled calendar rolls. A thermoplastic waterproofing membrane based on a polymer blend of ethylene vinyl acetate copolymer and linear low-density polyethylene (LLDPE) was used as the barrier layer in all seals.

[0197] The first starting composition containing the ingredients of the functional layer is melt processed in the first twin screw extruder. If the first starting composition contains a chemical foaming agent, the extruder is operated using a closed exhaust unit to prevent leakage of the foaming gas. The second starting composition containing the ingredients of the barrier layer is melt processed simultaneously in the second twin screw extruder and the first and second molten polymer compositions obtained are coextruded on top of each other through a flat die to produce a double-layer film composite material, which is subsequently cooled between calendering rolls. The gap between the calendering cooling rolls is adjusted to be slightly larger than the thickness of the coextruded film. The mass per unit area of ​​the functional layer changes from 582 to 651 g / m 2 And the thickness of the barrier layer is about 0.7 mm.

[0198] The operating conditions of the coextrusion equipment and the composition of the functional layers during the production of the sealing device are presented in Table 2. The extrusion temperature and pressure were measured at the point where the melt-processed mass enters the inlet of the flat die. The temperature of the cooling roll was approximately 20° C. during the production process.

[0199] The thickness of the barrier layer

[0200] The thickness of the barrier layer is determined by using the measuring method as defined in the DIN EN 1849-2 standard.A Keyence VHX-600 optical microscope with a magnification of 30 times is used to measure the thickness of the cross section.

[0201] Mass per unit area of ​​the functional layer

[0202] In order to determine the mass per unit area of ​​the functional layer of the sealing device, a reference film consisting of a barrier layer having the same thickness and composition as the barrier layer of the corresponding exemplary sealing device was first produced. Then 57 circular samples with a diameter of 8 cm were cut from the sealing device and the corresponding reference film. The mass of each sample was measured with an accuracy of 0.01 g and the mass per unit area was calculated by dividing the measured mass by the calculated area of ​​the sample. The functional layer coating weight of the sample cut from the sealing device was then determined by subtracting the mass per unit area of ​​the sample of the reference film from the mass per unit area of ​​the sample of the sealing device. Circular samples were cut from the sealing device and the reference film in the longitudinal direction along a length of about 5.5 m, with a distance of about 30 cm between adjacent samples.

[0203] Waviness Parameter and Waviness Factor

[0204] In order to characterize the surface roughness of the functional layer, sample strips having dimensions of 100 mm (length) × 100 mm (width) were cut from each of the produced sealing devices and adhered to a hard PVC sheet having dimensions of 100 mm (length) × 100 mm (width) × 5 mm (thickness), with the functional layer facing upward to ensure that the sample was completely flat. Double-sided tape was used when adhering the sample to the hard PVC sheet.

[0205] The surface geometry of the functional layer of each sample strip was measured using a 3D-scanner smartSCAN from AICON 3D Systems GmbH. The symbols in brackets in the following paragraphs refer to the terms used in the ISO 25178 standard.

[0206] The second-order polynomial fitted to the measured data points (F operator) was first subtracted from the surface geometry (extracted surface) to obtain the cross-sectional curve (SF surface). Then a cutoff length λ with a value of 0.8 mm was used. c (S filter) Obtain a waviness curve from the cross-sectional curve. Calculate the waviness parameter W according to ISO 25178 standard from the measured waviness curve Sq and W Spd (area parameter) and waviness factor W f Calculated as W Sq and W Spd Use Premium (V7) software (from DigitalSurf) is used to obtain the cross-sectional curve, waviness curve and waviness parameter W from the measured surface geometry. Sq and W Spd Required calculations.

[0207] Preparation of concrete test specimens

[0208] Three sample strips of dimensions 200 mm (length) x 50 mm (width) were cut from each of the sealing devices produced as described above. The sample strips were placed in a template having dimensions 200 mm (length) x 50 mm (width) x 30 mm (height) with the functional layer facing upward and the barrier layer (if present) against the bottom of the template.

[0209] One side of each sample strip on the functional layer side was covered with a tape having a length of 50 mm and a width corresponding to the width of the strip to prevent adhesion to the hardened concrete. The tape was used to make it easier to mount the test sample to the peeling resistance test equipment.

[0210] For the preparation of concrete specimens, a batch of fresh concrete formulation was prepared. The fresh concrete formulation was obtained by mixing 8.9900 kg of dry batch of MC 0.45 concrete according to EN 1766, 0.7440 kg of water and 0.0110 kg of Viscocrete 3082 in a drum mixer for five minutes. The MC 0.45 concrete dry batch contained 1.6811 kg of CEM I 42.5N cement (Normo 4, Holcim), 7.3089 kg of aggregate containing 3% Nekafill-15 (from KFN) concrete additive (limestone filler), 24% sand with a particle size of 0-1 mm, 36% sand with a particle size of 1-4 mm and 37% gravel with a particle size of 4-8 mm. The concrete dry batch was homogenized in a drum mixer for five minutes before blending with water and Viscocrete 3082.

[0211] The formwork containing the sample strips was then filled with fresh concrete formulation and vibrated for two minutes to release trapped gases. After 24 hours of hardening in standard atmosphere (air temperature 23°C, relative air humidity 50%), the test concrete specimens were peeled from the formwork and the concrete peeling resistance (early age adhesion strength) was measured.

[0212] Concrete stripping resistance

[0213] The peel resistance was measured according to the procedure specified in standard DIN EN 1372:2015-06. The peel resistance was measured using a Zwick Roell AllroundLine Z010 materials testing device equipped with a Zwick Roell 90° peel device (model 316237).

[0214] In the peeling resistance measurement, the concrete specimen is clamped by the upper clamp of the material testing equipment at the end of the concrete specimen containing the tape portion of the sample strip for a length of 10 mm. After that, the strip is peeled off from the surface of the concrete specimen at a peeling angle of 90° and a constant crosshead speed of 100 mm / min. The distance of the rollers during the test is about 570 mm. The peeling of the sample strip is continued until a strip of about 140 mm in length is peeled off from the surface of the concrete specimen. The peeling resistance value is calculated as the average peeling force / width of the sample strip [N / 50 mm] during the peeling process over a length of about 70 mm, so the first and last quarters of the total peeling length are excluded from the calculation.

[0215] The average peel resistance values ​​presented in Table 2 were calculated as the average of three measurements performed using the same sealing device.

[0216] Table 2

[0217]

[0218]

Claims

1. A sealing device (1) comprising a functional layer (2) having a first main surface and a second main surface and a barrier layer (3) directly or indirectly connected to the second main surface of the functional layer (2), the functional layer (2) comprising: a) 20-75% by weight of at least one thermoplastic polymer P1 and b) 25-80% by weight of at least one solid filler F, All ratios are based on the total weight of the functional layer (2), wherein The first main surface of the functional layer (2) has a waviness factor W of at least 0.0125 1 / mm. f Characterizing the surface roughness, the waviness factor W f RMS roughness W as waviness Sq and the peak density of the waviness W Spd The product of is determined by the waviness parameter W Sq and W Spd According to ISO 25178, the cut-off length λ is used c Determined by the waviness curve obtained for a measured cross-sectional curve of 0.8 mm; and The mass per unit area of ​​the functional layer (2) is 350–1000 g / m 2 ; The sealing device is produced by the following method: the method comprises the steps of extruding or co-extruding a first molten polymer composition comprising the components of the functional layer (2) through an extruder die, wherein the first molten polymer composition also contains a foaming gas, and the foaming gas is released from the first molten polymer composition through the surface of the functional layer (2) discharged from the extruder die, wherein the first molten polymer composition is obtained by melt processing a first starting composition comprising the components of the functional layer (2), wherein the first starting composition also contains at least one chemical foaming agent CBA, wherein the at least one chemical foaming agent CBA accounts for 0.1-2.0 wt% of the total weight of the first starting composition. 2 . The sealing device according to claim 1 , wherein the functional layer ( 2 ) comprises 25-70% by weight of at least one thermoplastic polymer P1 , based on the total weight of the functional layer ( 2 ). 3 . The sealing device according to claim 1 , wherein the functional layer ( 2 ) comprises 30-75% by weight of at least one solid filler F, based on the total weight of the functional layer ( 2 ).

4. The sealing device according to claim 1, wherein the first main surface of the functional layer (2) has a waviness factor W of at least 0.01351 / mm. f Characterizing the surface roughness, the waviness factor W f RMS roughness W as waviness Sq and the peak density of the waviness W Spd The product of is determined by the waviness parameter W Sq and W Spd According to ISO 25178, the cut-off length λ is used c The waviness curve was determined for a measured cross-sectional curve of 0.8 mm.

5. The sealing device according to claim 1, wherein the first main surface of the functional layer (2) has a waviness factor W of at least 0.0145 1 / mm. f Characterizing the surface roughness, the waviness factor W f RMS roughness W as waviness Sq and the peak density of the waviness W Spd The product of is determined by the waviness parameter W Sq and W Spd According to ISO 25178, the cut-off length λ is used c The waviness curve was determined for a measured cross-sectional curve of 0.8 mm.

6. The sealing device according to claim 1, wherein the particles of the at least one solid filler F are distributed over the entire volume of the functional layer (2).

7. The sealing device according to any one of claims 1 to 6, wherein the at least one solid filler F is selected from the group consisting of inert inorganic fillers, inorganic binders and synthetic organic fillers.

8. The sealing device according to any one of claims 1 to 6, wherein the at least one solid filler F comprises at least one inert inorganic filler F1 selected from sand, granite, calcium carbonate, clay, expanded clay, diatomaceous earth, pumice, mica, kaolin, talc, dolomite, xonotlite, perlite, vermiculite, wollastonite, barite, magnesium carbonate, silicon dioxide, fumed silica, fused silica, aerogel, glass beads, hollow glass spheres, ceramic spheres, bauxite, crushed concrete and zeolite.

9. The sealing device according to any one of claims 1 to 6, wherein the functional layer (2) further comprises at least one surfactant SF.

10. The sealing device according to claim 9, wherein the at least one surfactant SF is selected from glycerol monostearate, polycarboxylate ethers, polyether-modified polysiloxanes, polyalkylene oxide siloxanes, hydroxyethylamine, erucamide, stearyl stearamide, alkali metal alkanesulfonates and alkylarylsulfonates.

11. The sealing device according to any one of claims 1 to 6, wherein the barrier layer (3) has a first and a second main surface, wherein at least a portion of the first main surface of the barrier layer (3) is directly connected to the second main surface of the functional layer (2).

12. The sealing device according to any one of claims 1 to 6, wherein the barrier layer comprises at least 50% by weight of at least one thermoplastic polymer P2.

13. The sealing device according to any one of claims 1 to 6, wherein the barrier layer comprises at least 65% by weight of at least one thermoplastic polymer P2.

14. A method for producing a sealing device, the method comprising the steps of extruding or co-extruding a first molten polymer composition comprising the components of a functional layer (2) as defined in any one of the preceding claims through an extruder die, wherein the first molten polymer composition also contains a foaming gas, and the foaming gas is released from the first molten polymer composition through the surface of the functional layer (2) discharged from the extruder die, wherein the first molten polymer composition is obtained by melt processing a first starting composition comprising the components of the functional layer (2), wherein the first starting composition also contains at least one chemical foaming agent CBA, wherein the at least one chemical foaming agent CBA accounts for 0.1-2.0 weight % of the total weight of the first starting composition.

15. The method according to claim 14, wherein the at least one chemical blowing agent CBA is selected from azodicarbonamide, azobisisobutyronitrile, azocyclohexanecarbonitrile, dinitrosopentamethylenetetramine, azodiaminobenzene, calcium azide, 4,4'-diphenyldisulfonyl azide, benzenesulfonylhydrazide, 4,4-oxybenzenesulfonylsemicarbazide, 4,4-oxybis(benzenesulfonylhydrazide), diphenylsulfone-3,3-disulfonylhydrazide, p-toluenesulfonylhydrazide, p-toluenesulfonylsemicarbazide, trihydrazinotriazine, N,N'-dimethyl-N,N'-dinitrosoterephthalamide, diazoaminobenzene, diazoaminotoluene, hydrazonodicarbonamide, barium azodicarboxylate, 5-hydroxytetrazole, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate, potassium bicarbonate and an organic acid.

16. The method according to claim 14 or 15, wherein the at least one chemical blowing agent CBA represents 0.15-2.0 wt. % of the total weight of the first starting composition.

17. The method according to claim 14 or 15, wherein the at least one chemical blowing agent CBA represents 0.2-2.0 wt. % of the total weight of the first starting composition.

18. A method according to claim 14 or 15, comprising the further step of extruding or co-extruding through an extruder die a second molten polymer composition comprising the ingredients of the barrier layer (3) as defined in any one of claims 1 to 16.

19. The method according to claim 18, wherein the second molten polymer composition is obtained by melt processing a second starting composition comprising the ingredients of the barrier layer (3).

20. Sealing device obtainable by use of a method according to any one of claims 14-19.

21. Use of a sealing device according to any one of claims 1 to 13 or 20 for waterproofing a substrate.